PERAN KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL DALAM MENINGKATKAN KINERJA AUDITOR - WIJAYANTI, GERSONTAN LEWI (Universitas Katolik Widya Mandala Surabaya, 2012)
Along with increasing competition in the world of business requires companies to be able to present the financial statements are reliable and accountable to stakeholders. Hence the need for auditors in the world of professional services business in Indonesia experienced rapid development. In order to meet the needs and responsibilities, a professional auditor is required to improve the performance of the profession. An auditor who achieves good performance will improve client satisfaction, credibility and existence. An auditor as an independent should be able to improve performance. To improve performance, is associated with independent, an auditor also need emotional and spiritual intelligence. That by having the emotional intelligence of an auditor may have a good self-management, so that will affect every act of the play, and even in taking a decision. By having an auditor spiritual intelligence can do the values of truth and as a medium for self-evaluation, thus making the auditor's ability to repair and improve its performance. Therefore, emotional intelligence and spiritual intelligence should be developed to face stiff competition and the work of an auditor is compleks